THE ORIGINAN DEVOLUTION OF THE INTERSTITIAL CELLS AND OF THE OVARY AND THE SIGNIFICANCE OF THE DIFFERENT INTERNAL SECRETIONS OF THE OVARY - RAMIREZ, ELISEO; OCHOTERENA, ISAAC (MEXICO, CD. MEXICO, DF, MEX, 1920)
In the ovary two functions may be distinguished, one in relation to reproduction and consisting of the development of ova and the other referring to its role as an organ of internal secretions. From this point of view two sorts of histological structures
ENDOCRINOLOGY
Keywords: ORIGINAN, DEVOLUTION, INTERSTITIAL, CELLS, OVARY, SECRETIONS; CIENCIAS MEDICAS; MEDICINA INTERNA; ENDOCRINOLOGIA